2007
DOI: 10.1063/1.2464093
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of methyl chloride studied by partial positive and negative ion-yield spectroscopy

Abstract: The authors present partial-ion-yield experiments on the methyl chloride molecule excited in the vicinity of the Cl2p and C1s inner shells. A large number of fragments, cations produced by dissociation or recombination processes, as well as anionic species, have been detected. Although the spectra exhibit different intensity distributions depending on the core-excited atom, general observations include strong site-selective fragmentation along the C-Cl bond axis and a strong intensity dependence of transitions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…The general appearance of the partial yield spectra in the energy region below threshold is quite similar, but there are some significant differences which can aid in achieving a detailed spectral assignment. By comparing the partial yields shown in Fig.2, we notice an effect we have reported for several other systems [27,28], and namely that the relative intensity of the Rydberg series is higher for the smaller fragments. This is due to the fact that the excitations to Rydberg states decay mainly through spectator processes, and therefore the final states are mostly dissociative in nature.…”
Section: K-edgementioning
confidence: 81%
See 2 more Smart Citations
“…The general appearance of the partial yield spectra in the energy region below threshold is quite similar, but there are some significant differences which can aid in achieving a detailed spectral assignment. By comparing the partial yields shown in Fig.2, we notice an effect we have reported for several other systems [27,28], and namely that the relative intensity of the Rydberg series is higher for the smaller fragments. This is due to the fact that the excitations to Rydberg states decay mainly through spectator processes, and therefore the final states are mostly dissociative in nature.…”
Section: K-edgementioning
confidence: 81%
“…Formation of N + 2 requires a strong rearrangement of the molecular structure as it involves the breaking of two triple bonds between the nitrogen and the carbon atoms and the formation of a new bond between the two nitrogen atoms. Other examples of intramolecular atomic rearrangement were previously observed, involving the breaking of a H-X bond and formation of another bond during the reconfiguration of the electronic structure of the molecule following photoionization: formation of H [28]. In both of these examples, rearrangement is possible due to the high mobility of protons and is aided by vibrational excitation.…”
Section: Formation Of N +mentioning
confidence: 87%
See 1 more Smart Citation
“…Mass spectra recorded with respect to the incident polarization vector were used to confirm the symmetry of the 8a 1 antibonding LUMO. Several other studies have shown [8][9][10] fast fragmentation of the molecule after core excitation near the Cl L 2, 3 edge, leading to the formation of either Cl + or HCl + . The Auger-Doppler shift also has been observed for various orientations of the electron and fragment ion.…”
Section: Introductionmentioning
confidence: 97%
“…9 Partial-ion-yield experiments on CH 3 Cl excited in the vicinity of the Cl 2p inner shell have shown site-selective fragmentation along the C-Cl bond axis and strong intensity dependence of Rydberg transitions on fragment size. 7,10 Resonant inelastic x-ray scattering (RIXS), on the other hand, is a powerful tool for elucidating the electronic properties of gas-phase molecules. The physical process underlying RIXS corresponds to resonant excitation of an inner-shell electron followed by relaxation of the core-hole via radiative decay, i.e., x-ray photon emission.…”
Section: Introductionmentioning
confidence: 99%